A Wideband Ultra-Low-Profile Solar Cell–Integrated Antenna - Ali, Ahmed; Wang, Heesu; Yun, Yeojun; Park, Sungjun; Park, Yong Bae; Lee, Jaejin; Park, Ikmo (Journal of Electromagnetic Engineering and Science, 2023)
In this paper, a wideband ultra-low-profile solar cell–integrated antenna with a high form factor is presented. A copper indium gallium selenide-based solar cell was used for the proposed design. The solar cell was cut with a rectangular-shaped narrow slit to construct a built-in solar cell antenna with dimensions of 50 mm × 20 mm × 0.571 mm (0.382λo × 0.152λo × 0.0043λo at 2.28 GHz). The slit area needed to achieve a high form factor was only 0.5 mm × 18 mm. A coaxial-to-microstrip-line transition type of feeding structure was used to excite the antenna. An RF decoupler circuit was also designed under the second substrate to maintain the independent functioning of both devices. The simulated and measured results are in good agreement. Furthermore, the proposed design demonstrated a –10 dB impedance bandwidth of 42.45% with an ultra-low-profile structure of 0.0043λo at 2.28 GHz, and the maximum gain was 2.84 dBi in the impedance bandwidth range. In addition, the antenna has a high form factor of 99.1%, with no optical blockage
Keywords: Integrated Antenna; IoT Devices; Slit Antenna; Solar Cell; Ultra-Low-Profile Antenna; Wideband Antenna